'It all started here, and it all ends here too': Homosexual criminalisation and the queer politics of apology. (November 2020) - Redd, Curtis; Russell, Emma K
In recent years, we have witnessed a tide of government apologies for historic laws criminalising homosexuality. Complicating a conventional view of state apologies as a progressive effort to come to terms with past mistakes, queer theoretical frameworks help to elucidate the power effects and self-serving nature of the new politics of regret. We argue that through the discourse of gay apology, the state extolls pride in its present identity by expressing shame for its 'homophobic past'. In doing so, it discounts the possibility that systemic homophobia persists in the present. Through a critical discourse analysis of the 'world first' gay apology from the parliament of the Australian state of Victoria in 2016, we identify five key themes: the inexplicability of the past, the individualisation of homophobia, the construction of a 'post-homophobic' society, the transformation of shame into state pride and subsuming the 'unhappy queer' through the expectation of forgiveness.